2001
DOI: 10.1046/j.1365-2133.2001.04071.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates of Breslow thickness of malignant melanoma

Abstract: Results were similar for the two thickness groups, but more significant for the thick group. The previously described correlations of tumour thickness and increasing age (P < 0.00001) and location on head and neck (P = 0.0002), together with the independence of these variables, have been confirmed. The correlation with male gender was also confirmed but this was weak (P = 0.05). Novel findings were correlations of Breslow thickness with all features of the seven-point checklist (P varying from P = 0.01 to P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 30 publications
6
33
1
Order By: Relevance
“…Several studies showed that Breslow thickness is associated with male gender [30], [31]. This finding was confirmed by our study.…”
Section: Resultssupporting
confidence: 92%
“…Several studies showed that Breslow thickness is associated with male gender [30], [31]. This finding was confirmed by our study.…”
Section: Resultssupporting
confidence: 92%
“…Although research has been performed investigating the relationship between surgical delay and tumor growth in melanoma patients, [23][24][25][26][27] few studies have looked at this same effect for the treatment of NMSC. Kirkup and De Berker examined 50 patients with BCC of the face, but outside the "central T" (nose and periorbital areas, including eyebrows and glabella), and compared major and minor diameters at presentation and again on the day of surgery.…”
Section: Discussionmentioning
confidence: 97%
“…On the basis of Breslow thickness, patients were divided into five conventional Breslow thickness groups (0 -4); in situ, o0.75 mm, 0.75 -1.49 mm, 1.5 -3.49 mm and X3.5 mm (Mackie et al, 1985). For the occurrence studies, a subsample of patients were stratified according to Breslow thickness group to conform with frequencies within groups according to the reported distribution in the Leicestershire area (n ¼ 738) (Osborne and Hutchinson, 2001). Controls consisted of UK Caucasian patients not known to have cancer.…”
Section: Studiesmentioning
confidence: 99%